2020
DOI: 10.1039/d0cp03286g
|View full text |Cite
|
Sign up to set email alerts
|

Solvent oligomerization pathways facilitated by electrolyte additives during solid-electrolyte interphase formation

Abstract: The solid-electrolyte interphase (SEI) layer formation is known to play an important role in determining the lifetime of lithium-ion batteries. A thin, stable SEI layer is linked to overall improved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…, C, O, H, and F A previous computational study from our group showed through reaction network analysis that PEC and PEO are the most thermodynamically favorable products of EC decomposition via SN1 and SN2 reaction pathways, respectively. 36 As can be seen from Table 1, the SN2 oligomerization pathway is exothermic for all surfaces examined, while the SN1 pathway is only exothermic for pristine graphite, hydroxyl, and ketonic surfaces. The most exothermic SN2 decomposition for EC is on the carbonyl surface, which in combination with the highly endothermic SN1 reaction energies, implies that EC decomposition on the carbonyl surface would result in high PEO content.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…, C, O, H, and F A previous computational study from our group showed through reaction network analysis that PEC and PEO are the most thermodynamically favorable products of EC decomposition via SN1 and SN2 reaction pathways, respectively. 36 As can be seen from Table 1, the SN2 oligomerization pathway is exothermic for all surfaces examined, while the SN1 pathway is only exothermic for pristine graphite, hydroxyl, and ketonic surfaces. The most exothermic SN2 decomposition for EC is on the carbonyl surface, which in combination with the highly endothermic SN1 reaction energies, implies that EC decomposition on the carbonyl surface would result in high PEO content.…”
Section: Resultsmentioning
confidence: 82%
“…In vacuum, both SN1 and SN2 oligomerization pathways have been found to be exothermic. 36 Coupled with CO2 generation, oligomerization through an SN2 pathway results in alkoxide regeneration, which is responsible for continual polymerization reactions along the electrode surface, as is observed in experiment. 34 In addition to the polarity of the electrolyte species, SEI formation is also found to be highly sensitive to the surface structure of electrodes.…”
Section: Figure 1: Oligomerization Products Of Ec and Fec Through Sn1 And Sn2 Decomposition Pathwaysmentioning
confidence: 83%
See 2 more Smart Citations
“…However, even very reactive molecules can often be studied using first-principles quantum chemical methods such as density functional theory (DFT). Such computational simulations can therefore fill a gap and potentially provide a more fundamental understanding of the reactive chemistry of the SEI -for instance through the calculation of reaction free energies and energy barriers [8][9][10][11][12] . DFT can additionally be used to generate reference spectra that can be compared to experiment 13 .…”
Section: Background and Summarymentioning
confidence: 99%